Marine ecological and environmental health assessment using the pressure-state-response framework at different spatial scales, China - Wei Yang (Elsevier, 2021)
Coastal seas are sensitive marine ecosystems, subject to stress from human activities and climate change. Understanding their health is therefore essential. In this study, we developed a comprehensive marine health assessment index (MHI) system using the pressure-state-response framework, and used it to explore the temporal and spatial differences in marine health for 4 Chinese seas and 11 coastal regions of these seas. The South China Sea was relatively healthy, with an average MHI score of 0.72; the other coastal regions were moderately healthy, with MHI of 0.60 for the Yellow Sea, 0.59 for the Bohai Sea, and 0.56 for the East China Sea. At a provincial scale, Hainan’s coastal sea was relatively healthy. Guangdong, Shanghai, Tianjin, Liaoning, and Shandong had relatively healthy coastal seas; the others were moderately healthy. The overall health of most seas and provincial coasts decreased from 2003 to 2018. However, MHI increased by 10.6% in the East China Sea, versus 16.4 and 6.7% (respectively) for the Shanghai and Zhejiang coastal seas in the East China Sea, and a decrease of 4.9% for the Fujian coastal sea. The Bohai Sea MHI decreased by 1.6%, but Tianjin’s MHI increased by 1.7%. Therefore, the MHI trends were inconsistent between the regional and provincial scales. Marine disasters and environmental factors caused large MHI changes at a regional scale, whereas human factors were more important at the provincial scale. Our results show that an assessment’s spatial scale strongly affects the key factors that will be identified. Our results will help marine managers assess marine health at different spatial scales to support marine protection planning.